The effect of self-congruity and emotional attachment on revisit intention in Penglipuran village as an alternative tourism destination - Pande Gde Bagus Naya Primananda; I Made Suniastha Amerta; A.A Made Indra Wijaya Kusuma (Jurnal Pariwisata Pesona, 2026)
The tourism trend has recently shifted from mass tourism to alternative tourism. Alternative tourism emphasizes the quality of travel experiences while minimizing environmental degradation. One form of alternative tourism is the tourism village. A tourism village refers to a rural administrative area that possesses distinctive potential and unique attractions, offering visitors the opportunity to experience the lifestyle, traditions, and authenticity of rural communities and their local resources. The problem addressed in this study arises from the tendency of tourists to visit Southern Bali, which results in unstable visitor numbers in Northern Bali, further intensified by competition among alternative tourism destinations in the region. This study aims to analyze the effect of self-congruity on revisit intention with emotional attachment as a mediating variable among visitors to Penglipuran Village. A quantitative approach was employed, involving 110 domestic tourists and travelers who visited Penglipuran Village. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that self-congruity significantly influences revisit intention, self-congruity significantly affects emotional attachment, and emotional attachment significantly influences revisit intention. Furthermore, emotional attachment serves as a partial mediator in the relationship between self-congruity and revisit intention. Theoretically, this study contributes novelty by employing cognitive, affective, and conative perspectives to measure self-congruity, emotional attachment, and revisit intention, respectively. From a managerial perspective, the findings suggest that the management of Penglipuran Village should recognize that many tourists aspire to live in an environment similar to that of Penglipuran. This implies that the cultural values and atmosphere of Penglipuran Village play a crucial role in attracting tourists and fostering their emotional connection to the destination.